Manfaat Penambahan Metode Centering Pada Program Fisioterapi Terhadap Peningkatan Kapasitas Fungsional Penderita Osteoarthritis Genu: Studi Kasus - M H Indra Prana (Journal of Health and Therapy, 2022)
Osteoarthritis genu is the most common arthritis in elderly which is degenerative and chronic due to damage to the knee joint. Genu osteoarthritis is one of the factors in the decline in the quality of life index. One indicator of quality of life index is the ability of functional capacity. Measurement of functional capacity using the womac index. Increased functional capacity using the centering method by combining with exercise therapy. This study aims to determine the benefits of providing a centering method in a physiotherapy program to increase the functional capacity of genu osteoarthritis sufferers. The type of research used in this study is a single research study with a quantitative case study and the research design used is Pretest-posttest A-B-A Design by combining centering training with exercise therapy. the results show there was an increase in functional capacity in genu osteoarthritis sufferers after combining the centering method with the physiotherapy program.